A Novel Logistics Optimisation Module for Improving Response Deployment of Critical Resources - Filippas, Evangelos; Kumar, Akhil Sai Ravi; Ali, Muhammad; Ziemian, Sabina; Kostaridis, Antonios (Proceedings of the International ISCRAM Conference, 2026)
Effective crisis response requires both situational awareness and efficient coordination of logistics resources across multiple agencies. While Command, Control, Communications and Intelligence / Incident Management Systems (C3I/IMS) provide a Common Operational Picture (COP) and vehicle dispatching, they lack embedded optimisation capabilities for dynamic routing and allocation. This work operationalises logistics optimisation within a real C3I/IMS by introducing a module that formulates response logistics as a Multi-Depot Capacitated Vehicle Routing Problem with heterogeneous fleet characteristics, inventory coupling, compatibility constraints, and explicit time components. The module functions as an event-driven intelligence layer, automatically generating allocation plans, geospatial routes, Estimated Time of Arrival (ETA) predictions, and diagnostic outputs. A synthetic civil protection scenario demonstrates system integration and workflow coherence. The contribution lies in embedding optimisation-driven logistics intelligence within a multi-agency command-and-control environment, improving response efficiency, transparency, and interoperability, while also supporting preparedness through integrated simulation capabilities.